Staff development seminar/workshop : Delivering the UNIMAS mission, 2-3 October 1993, Riverside Majestic Hotel Kuching - Universiti Malaysia, Sarawak (1993)
Jointly organised by Universiti Malaysia Sarawak, Higher Education for Capability and Sarawak Economic Development Corporation.